Tax Evasion and Non-oil Revenue Administration in Nigeria - Femi-Ayegbo, Toluwabori Blessing; Omodero, Cordelia Onyinyechi (Journal of Legal Studies, 2025)
The relationship between tax evasion and non-oil revenue in Nigeria was investigated in this study. The study’s specific objectives were to investigate how corruption perception index and revenue leakages through tax evasion impact non-oil revenue in Nigeria. Secondary monthly data from 2015M1 till 2022M12 and the study's data were taken from the Central Bank of Nigeria's annual reports and the Nigerian Federal Inland Revenue Services' yearly reports. The sourced data was estimated using the multiple regression technique. The unit root test showed that all the variables were stationary at levels. Findings showed that corruption perception index and revenue leakages through tax evasion negatively and significantly impact non-oil revenue in Nigeria. Therefore, the research suggested that in order to penalize those who commit tax evasion, the government's tax rules should be examined on a regular basis.